2018
DOI: 10.1016/j.envres.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NOx emissions of a retrofitted Euro 5 passenger car for the Horizon prize “Engine retrofit”

Abstract: The Horizon 2020 prize for the “Engine Retrofit for Clean Air” aims at reducing the pollution in cities by spurring the development of retrofit technology for diesel engines. A Euro 5 passenger car was retrofitted with an under-floor SCR (Selective Catalytic Reduction) for NOx catalyst in combination with a solid ammonia based dosing system as the NOx reductant. The vehicle was tested both on the road and on the chassis dynamometer under various test cycles and ambient temperatures. The NOx emissions were redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Owing to the low NH 3 emissions measured from DV2 on all tested conditions, it is assumed that, in addition to LNT and SCR, it was also equipped with an ammonia slip catalyst (ASC). Similar efficiency at removing NH 3 using ASC was recently shown for a Euro 5 and a Euro 6 diesel vehicle retrofitted with a solid ammonia reduction system [55,56]. NH 3 emissions from DV1 on the RDE-compliant Route-1 were 2.4-5.7 times higher than those reported from an SCR-equipped Euro 6b diesel vehicle tested on-road on an RDE compliant route [31].…”
Section: On-road Emissions From the Diesel Vehiclessupporting
confidence: 71%
See 1 more Smart Citation
“…Owing to the low NH 3 emissions measured from DV2 on all tested conditions, it is assumed that, in addition to LNT and SCR, it was also equipped with an ammonia slip catalyst (ASC). Similar efficiency at removing NH 3 using ASC was recently shown for a Euro 5 and a Euro 6 diesel vehicle retrofitted with a solid ammonia reduction system [55,56]. NH 3 emissions from DV1 on the RDE-compliant Route-1 were 2.4-5.7 times higher than those reported from an SCR-equipped Euro 6b diesel vehicle tested on-road on an RDE compliant route [31].…”
Section: On-road Emissions From the Diesel Vehiclessupporting
confidence: 71%
“…In the dynamic tests, NO x emissions were~3.5 times higher than in the RDE compliant tests. Higher emissions during dynamic operation compared to "normal" driving have previously been reported for Euro 6b diesel vehicles equipped with SCR and LNT systems [55]. Although NO x emissions from vehicles type-approved using RDE have been improved overall, the relatively high emissions measured from the two Euro 6d-TEMP diesel vehicles during dynamic driving and on the motorway section illustrate that there are still operating conditions that could be improved.…”
Section: On-road Emissions From the Diesel Vehiclesmentioning
confidence: 84%
“…The differences for the SI vehicle were within 5 mg/km, while for the CI vehicle, the scatter was up to ±40 mg/km, although most of the results were within ±20 mg/km or ±15%. Other PEMS validation studies have found differences of around 15% at the 20 mg/km NO x range (i.e., differences around 3 mg/km) [12,13] and around 10% at the 500 mg/km NO x range [11,16].…”
Section: No X Distance Specific Resultsmentioning
confidence: 99%
“…Most researchers have found differences below 3.6% [11][12][13]15,16] for CO 2 mass emissions, and one study found a difference of 8% for one PEMS [13] compared with the laboratory equipment. The higher differences found in this study have to do with the higher flow rate uncertainties discussed previously (Figure 3).…”
Section: No X Concentrations Comparisonmentioning
confidence: 99%
“…In 2015, nearly 39% of nitrogen dioxides produced in the European Union was from the transportation sector. Significant nitrogen monoxide emissions [2] and 50% of PM are generated by diesel engines [3]. To clarify, diesel engine emissions can be divided into gaseous precursors (NOx, H 2 SO 4 , SO 3 , SO 2 , H 2 O, low-volatile, and semi-volatile organic compounds), and solid carbonaceous material such as PM [2][3][4].…”
Section: Introductionmentioning
confidence: 99%